?DATURA METEL L. A PLANT WITH NEMATICIDAL POTENTIAL - QAMAR, F.; KAPADIA, Z.; KHAN, S.A; BADAR, Y. (Biological Sciences - PJSIR, 1995)
Nematicidal activities of Datura metel L. leaves extracted in various solvents were tested. A sample of total alkaloids content and a sample of hyoscine extracted from D. metelleaves were also assayed for their nematicidal action.Hoplolaimus indicus (Sher, 1963),Helicotylenchus multicinctus (Cobb, 1893; Golden, 1956)andMeloidogyne incognita (Kofoid and White 1919;Chitwood, 1949)were selected as test nematodes. It has been observed that total alkaloidsshowed90-100%mortalityforallthetestnematodes,whereashyoscinewaseffectiveonly againstHoplolimus indicus, showing 90% mortality.